Sentidos e significados atribuídos ao gênero correspondência oficial - ofício - em diálogo intercultural - Souza, Maria de Lourdes Albuquerque de (2012)
This research has as main objective to create moments of critical reflection with the researched group looking for the comprehension and discussion of the organization and use of the official correspondence genre - correspondência oficial ofício, an official document that is commonly received from non- indigenous institutions for kaiowá leaderships and teachers from T. I. Panambizinho. This study is based theoretically in the Socio-Historical- Cultural Activity Theory (Vygotsky, Leontiev, Engeström) and the discussions of Bakhtin about discourse genres; in Magalhães (2004), Liberali (2009), Kerbrat-Orechioni (2010), Brookfield & Preskill (2005), Smyth (1992) and Mackay (1980), in order to analyze the organizational pattern of language in the turn-taking in the discussions. The methodological orientation is anchored in the Critical Research of Collaboration, which points to the organization of language as dialogical and dialectic in the accomplishment of a joint work by the participants. As pointed out by Magalhães (2007a) it is about a methodology of intervention in the context of accomplishment of the research, with the objective to create spaces of joint construction for the understanding and transformation of senses attributed to the object under discussion and production of shared meanings. This study was carried out with leaderships and teachers of the Indigenous Land, Panambizinho, Dourados/MS. The data was collected/produced, through workshops of study, with focus in the reading and writing of the official correspondence genre, correspondência oficial ofício, that were recorded in audio and video. The focus of this dissertation is on the reading. The results had disclosed no initial understanding of the indigenous participants on the importance and use of the official correspondence ofício, in their relations with the non-indigenous institutions. It also revealed the collaborative production of meanings during the two days workshops, as well as the partial transformation of them, made possible by the construction of a collaborative interactional pattern, where all the participants shared the object of the activity and revealed themselves committed to participate in the discussions. The sharing of meanings, as to the understanding and use of the official correspondence ofício by kaiowá participants, will only be possible to be evidenced at the subsequent moment to the accomplishment of this research